2011
DOI: 10.1111/j.1758-2229.2011.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of poly(3‐hydroxybutyrate) synthesis in catabolite repression of tetralin biodegradation genes in Sphingomonas macrogolitabida strain TFA

Abstract: The tetralin biodegradation genes of Sphingomonas macrogolitabida strain TFA are repressed by catabolite. Insertion mutants in which thn genes are transcribed in the presence of a preferential carbon source and tetralin, bear the insertion in phaC, encoding a poly(3-hydroxybutyrate) (PHB) synthase, a key enzyme in PHB synthesis. Mutant complementation with phaC genes from either Ralstonia euthropha or TFA restored PHB accumulation and the wild-type regulatory pattern of thn genes, thus indicating that this acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although PHB synthesis and degradation were incorporated into iIG743, all predictions were performed without synthesis of this carbon storage granule. However, it has been reported previously that TFA cells accumulate PHB up to approximately 7% of the total biomass dry weight during growth in minimal medium plus 40 mM 3-HB 41 . As observed in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Although PHB synthesis and degradation were incorporated into iIG743, all predictions were performed without synthesis of this carbon storage granule. However, it has been reported previously that TFA cells accumulate PHB up to approximately 7% of the total biomass dry weight during growth in minimal medium plus 40 mM 3-HB 41 . As observed in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 82%
“…However, a clear connection between CCR and the energetic status of the cell has been demonstrated in this bacterium (Figure 4). Transposon mutants affecting in phaC gene, coding for a poly(3-hydroxybutyrate) synthase, are unable to synthetize the carbon storage PHB (polyhydroxybutyrate) granule and show a partial release of thn genes CCR [56]. Conversely to what happens in the wild-type, phaC mutants prematurely induce thn genes in the presence of βHB, although maximal induction is never reached.…”
Section: Regulation Of the Thn Gene Expressionmentioning
confidence: 99%
“…The lack of SuhB or Hfq provokes a premature induction of thn genes in CCR conditions. However, only partial induction, even lower than that reached in phaC mutants, is achieved [56,57]. It has been demonstrated that suhB expression is regulated by the growth rate, being elevated at high growth rates, which would imply a high-energy status of the cells.…”
Section: Regulation Of the Thn Gene Expressionmentioning
confidence: 99%
“…Moreover, induction of thn expression by tetralin is prevented in the presence of alternative and preferential carbon sources such as β-hydroxybutyrate (βHB) or sebacic acid (Martínez-Pérez et al, 2004), but the regulatory mechanism that underlies this CCR was unknown. An extensive search for transposon mutants that expressed thn genes in CCR conditions resulted in the identification of a negative role for the polyβ-hydroxybutyrate (PHB) granule synthesis in thn gene expression (Martín-Cabello et al, 2011). Mutants lacking the PHB synthase PhaC showed partial de-repression of thn expression in CCR conditions due to the absence of the polymer, which seems to be sensed as a signal for carbon sufficiency.…”
Section: Introductionmentioning
confidence: 99%